Increasing Drug Resistance Among Persons With Tuberculosis in Massachusetts, 2009–2018. (18th July 2020) - Eddy, Jared J; Gadani, Kavita M; Tibbs, Andrew; Bernardo, John; Cochran, Jennifer; White, Laura F; Horsburgh, C Robert; Jacobson, Karen R
Abstract: We examined Massachusetts tuberculosis surveillance data from to 2009 to 2018. Of 1533 culture-confirmed cases, 190 (12.4%) demonstrated resistance to isoniazid including 32 (2.1%) with rifampin resistance. In multivariable analysis, isoniazid resistance increased significantly over time (per-year odds ratio = 1.07, 95% confidence interval = 1.01–1.13, P = .018) and was associated with younger age, foreign birth, and prior tuberculosis treatment.